Impact of Bamlanivimab Monoclonal Antibody Treatment on Hospitalization and Mortality Among Nonhospitalized Adults With Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (17th May 2021) - Bariola, J Ryan; McCreary, Erin K; Wadas, Richard J; Kip, Kevin E; Marroquin, Oscar C; Minnier, Tami; Koscumb, Stephen; Collins, Kevin; Schmidhofer, Mark; Shovel, Judith A; Wisniewski, Mary Kay; Sullivan, Colleen; et al.
Abstract: Background: Monoclonal antibody treatment may prevent complications of coronavirus disease 2019 (COVID-19). We sought to quantify the impact of bamlanivimab monoclonal antibody monotherapy on hospitalization and mortality among outpatients at high risk of COVID-19 complications. Methods: In this observational study we compared outpatients who received bamlanivimab monoclonal antibody from December 9, 2020 to March 3, 2021 to nontreated patients with a positive polymerase chain reaction or antigen test for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during the same period who were eligible for monoclonal antibody treatment. The primary outcome was 28-day hospitalization or all-cause mortality, and the secondary outcome was hospitalization or emergency department visit without hospitalization. The risk-adjusted odds of study outcomes comparing bamlanivimab treated and untreated patients was determined using 1:5 propensity matching and multivariable logistic regression. Results: Among 232 patients receiving bamlanivimab matched with 1160 comparator patients, the mean age was 67 years, 56% were female, and 196 (14%) of patients experienced hospitalization or mortality. After adjustment for propensity to receive treatment, bamlanivimab treatment was associated with a significantly reduced risk-adjusted odds of hospitalization or mortality within 28 days (odds ratio [OR], 0.40; 95% confidence interval [95% CI], 0.24–0.69; P < .001). Bamlanivimab treatment was also associated with a significantly lower risk adjusted odds of hospitalization or emergency department visit without hospitalization (OR, 0.54; 95% CI, 0.35–0.82; P = .004). The results were most strongly associated with patients age 65 years and older. Conclusions: Bamlanivimab monoclonal antibody monotherapy was associated with reduced hospitalizations and mortality within 28 days among outpatients with mild to moderate COVID-19. Use of bamlanivimab monotherapy for outpatients with mild to moderate COVID-19 infection was associated with reductions in hospitalizations and mortality within 28 days. Benefit was strongest in those age 65 years or older